The Effect of Friction Spot Stir Welding in Installing Double Cover Rivet Lap Joints on Aluminum 2024 – T3 and 7075 – T6 with Mechanical Strength - Sehono, Sehono; Wibisono, Febrian Adi; Putra, Ikbal Rizki (Jurnal Rekayasa Mesin, 2026)
Selection and treatment of materials in the aerospace, marine, transportation, and manufacturing industries are crucial for achieving efficient configurations. Aluminum is one of the materials widely used in these industries due to its lightweight, corrosion resistance, and good electrical conductivity properties. Aluminum alloys 2024-T3 and 7075 are often used in aircraft component manufacturing due to their strength and excellent corrosion resistance. The commonly used joining method is riveting, but there are also other methods such as friction spot stir welding (FSSW). In this study, joining was performed using rivets and followed by the FSSW process on aluminum plates of types 2024 and 7075. The objective of this research is to investigate the mechanical strength of rivet joints combined with the FSSW process on plates with different types. A literature review on aluminum, alloys 2024-T3 and 7075-T6, as well as the riveting and FSSW joining methods, was also conducted. The experimental method involved joining the two types of plates using rivets and subsequently performing the FSSW process. The results of this research are expected to provide a better understanding of the mechanical strength of rivet and FSSW joints on aluminum plates with different types.